2014
DOI: 10.1002/jcb.24803
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Nuclear Localization of β‐Catenin in Normal and Malignant Tissue

Abstract: The canonical Wnt signaling pathway has been the focus of intensive research because of its frequent dysregulation in human cancers. Much of this has been directed towards the aberrant expression and/or activity of the central mediator of this pathway, β-catenin. In particular, the nuclear localization of β-catenin and subsequent inappropriate activation of TCF/LEF-mediated transcription appears to be an important process in both the establishment and maintenance of cancer stem cells. Despite this, the exact m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 91 publications
(96 reference statements)
0
56
1
Order By: Relevance
“…This observation fits well with the known relationship of p53, β-catenin and Ki67 in cell proliferation 28–30. β-Catenin is a key factor of Wingless Int-1 (WNT) signalling, and nuclear translocation of β-catenin characterises cells with active WNT signalling 31. Active WNT signalling leads to enhanced cell proliferation and, thus, to elevated Ki67LI.…”
Section: Discussionmentioning
confidence: 99%
“…This observation fits well with the known relationship of p53, β-catenin and Ki67 in cell proliferation 28–30. β-Catenin is a key factor of Wingless Int-1 (WNT) signalling, and nuclear translocation of β-catenin characterises cells with active WNT signalling 31. Active WNT signalling leads to enhanced cell proliferation and, thus, to elevated Ki67LI.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that ␤-catenin nuclear localization is the initiating and driving element in ␤-catenin signaling, and that this step is regulated independently of its stabilization (35). A number of previous studies demonstrated that GPCR activation regulates ␤-catenin function and localization, but the mechanism(s) involved remained incompletely defined (50).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of Wnt ligands to their receptor Frizzled and coreceptor LRP5/6 inactivates the ␤-catenin destruction complex (13), thereby promoting ␤-catenin cellular accumulation and nuclear import, association with T-cell factor/lymphoid enhancer factor (TCF/ LEF) transcription factors, and activation of target genes (13,33,63). It is increasingly recognized that ␤-catenin nuclear localization is the initiating and driving element in ␤-catenin signaling, and that this step is regulated independently of its stabilization (35). While NH 2 -terminal phosphorylation of ␤-catenin targets it to degradation, phosphorylation at Ser 552 and Ser 675 promotes its dissociation from cell-cell contacts, induces its nuclear localization, and stimulates its transcriptional activity via Wnt-independent pathways (11,16,17,27,30,41,60,61).…”
mentioning
confidence: 99%
“…Furthermore, ΔNp63 was expressed in the caudal gut endoderm and contributed to the stem/progenitor compartment of adult colorectal epithelium, which could also lead to (basaloid) squamous carcinoma of the anorectal mucosa 24. Another helpful marker for the differential diagnosis of BAC versus CAC is ß-catenin, a protein regulating cell adhesion and gene transcription mainly via the Wnt signalling pathway 25. Nuclear translocation of ß-catenin results from lacking cytoplasmic degradation of ß-catenin in tumours with a non-functional degradation complex, which includes APC (adenomatous polyposis coli-protein).…”
Section: Discussionmentioning
confidence: 99%